2003
DOI: 10.1177/089686080302300108
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Stability of Antimicrobial Activity in Peritoneal Dialysis Solutions

Abstract: ← Objective To evaluate the stability of the antimicrobial chemical and bioactivity of gentamicin, vancomycin, and gentamicin and vancomycin in combination, and the stability of the bioactivity of ceftazidime, admixed in standard peritoneal dialysis solutions and then maintained over a 14-day period at room temperature or under refrigeration. ← Setting Peritoneal dialysis center and microbiology laboratory at a military, teaching medical center. ← Measurements Standard peritoneal dialysate bags admixed with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Concerns about cefazolin and ceftazidime stability when exposed to the warmer for an extended time are alleviated by our stability experiment. Moreover, our in vitro experiment also confirmed that cefazolin and ceftazidime added in the 5-liter bag had a good stability in a refrigerator, similar to results from the previous studies in 2-liter bags (2632). The prolonged refrigerated antibiotic stability over many days would decrease the required frequency of delivering antibiotic-containing PD fluid to patients who live in remote areas and cannot aseptically add antibiotics to PD solutions by themselves.…”
Section: Discussionsupporting
confidence: 89%
“…Concerns about cefazolin and ceftazidime stability when exposed to the warmer for an extended time are alleviated by our stability experiment. Moreover, our in vitro experiment also confirmed that cefazolin and ceftazidime added in the 5-liter bag had a good stability in a refrigerator, similar to results from the previous studies in 2-liter bags (2632). The prolonged refrigerated antibiotic stability over many days would decrease the required frequency of delivering antibiotic-containing PD fluid to patients who live in remote areas and cannot aseptically add antibiotics to PD solutions by themselves.…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotics are stable for variable times after being added to the PD solution ( 327 ). Vancomycin is stable for 28 days in dialysis solutions stored at room temperature, although higher ambient temperatures will reduce the duration of stability.…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…The Committee recommends center-specific selection of empiric therapy, dependent on the local history of sensitivities of organisms causing peritonitis ( Opinion ). Gram-positive organisms may be covered by vancomycin or a cephalosporin, and gram-negative organisms by a third-generation cephalosporin or aminoglycoside ( Evidence ) (Figure 1) (65-105).…”
Section: Specimen Processingmentioning
confidence: 99%